Daemons of the shadow realm. 3 - Arakawa, Hiromu, 1973- (Square Enix Manga & Books, 2023)
Ancient Daemons awaken to fight a new battle in an age-old war!! To get some answers, Yuru warily accepts an invitation from the Kagemoris, the very people who assaulted his village. This soon turns into an uneasy alliance when an ambush threatens everyone's safety. But not even that surprise can prepare Yuru for Asa's story! What is the stark secret to claiming the twins' powers? And does Yuru have what it takes to confront what lies in the abyss...and beyond?